2007
DOI: 10.1097/mnm.0b013e3281744440
|View full text |Cite
|
Sign up to set email alerts
|

99mTc bone scintigraphy superscans: a review

Abstract: Whole-body bone scintigraphy (bone scan) using a (99m)Tc-labelled pharmaceutical is one of the most commonly performed radionuclide examinations. In the normal patient, both the osseous components of the skeletal system as well as the kidneys and bladder are visualized. A superscan is defined as a bone scan which demonstrates markedly increased skeletal radioisotope uptake relative to soft tissues, in association with absent or faint genito-urinary tract activity. While a superscan is relatively uncommon, its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 29 publications
0
38
0
3
Order By: Relevance
“…Los patrones gammagráficos más frecuentemente en los casos publicados en la literatura son aquellos con captaciones compatibles con fracturas por insuficiencia o pseudofracturas [2,3,9]. Sin embargo, en 3 de ellos se encontró un aumento generalizado de la incorporación del trazador en todo el esqueleto con ausencia o muy débil visualización de las siluetas renales, patrón conocido como "superscan" [4,5,6,19]. Las características clínicas de dichos casos se resumen en la Tabla 1.…”
Section: Discussionunclassified
“…Los patrones gammagráficos más frecuentemente en los casos publicados en la literatura son aquellos con captaciones compatibles con fracturas por insuficiencia o pseudofracturas [2,3,9]. Sin embargo, en 3 de ellos se encontró un aumento generalizado de la incorporación del trazador en todo el esqueleto con ausencia o muy débil visualización de las siluetas renales, patrón conocido como "superscan" [4,5,6,19]. Las características clínicas de dichos casos se resumen en la Tabla 1.…”
Section: Discussionunclassified
“…A commonly used SPECT radionuclide probe for the detection of infections and inflammatory disorders is 99m Tc-exametazime (hexamethylpropylene amine oxime, HMPAO). 77 Becerra et al 78 used 99m Tc-HMPAO to image distribution of stem cells in horses with occurring tendinopathy. Cells were injected either intravenously or directly into tendon or ligament injures or intravenously in horses and traced for up to 48 h, and 24% of the cells were retained within the tendon lesions.…”
Section: Current Stem Cell Imaging Technologiesmentioning
confidence: 99%
“…Wiegemann et al (2) reported that bone resorption, alkaline phosphatase level, and parathyroid hormone activity were not correlated with Tc-99m pyrophosphate uptake by the bone. Malignancies with known super scan in bone scintigraphy include prostate cancer, breast cancer, lung cancer, lymphoma, urinary tract transitional cell carcinoma, nasopharyngeal carcinoma and carcinoma of the colon (3,4,5). Hematologic conditions like leukemia, lymphoma, myelofibrosis, Waldenstrom's macroglobulinemia have also been reported to be associated with super scan.…”
Section: öZmentioning
confidence: 99%